Government systems - Sánchez Velásquez, Katia Cristina (2011)
Since ancient times, human beings have organized ourselves in more or less complex societies, around centers of power that most likely originated from family authority figures, whether maternal or paternal, so that in many cultures the king he was considered the father of the town; Since then, as social groups have increased in size and complexity, this figure of authority began to be exercised by defined social groups, such as the nobles, whose kinship with the monarch meant a privileged position within the community." Before the birth of democracy, most of the states were governed by the aristocracies, which, as we know, was the government of a small group of people who generally came from noble families.